Effect of ROA (Return On Assets), ROE (Return On Equity), NPM (Net Profit Margin), and EPS (Earning Per Share) on Stock Prices: Pengaruh ROA (Return On Assets), ROE (Return On Equity), NPM (Net Profit Margin), dan EPS (Earning Per Share) Terhadap Harga Saham - Inggit Faridatus Sholikah; Nurasik Nurasik (Academia Open, 2021)
Property business is currently one of the business prospects whose business characteristics tend to increase every year because land prices tend to increase every year. This research aims to determine whether stock prices can be influenced by the return on assets ratio (ROA), return on equity ratio (ROE), net income ratio (NPM) and earnings per share ratio (EPS). The entire property real estate sector is the population taken in this study, with a criterion sampling technique or purposive sampling so that a sample of 31 companies with observations for 3 years so that a total of 93 observations of financial statements from 31 selected samples are then calculated. research and tabulated and processed with the SPSS version 25 application, with a series of tests to strengthen the results of the hypothesis. In this research, the results of the study conclude that the first is that there is no effect of the return on assets ratio (ROA) on stock prices, secondly there is the effect of the ratio of return on equity (ROE) to stock prices, thirdly there is no effect of the ratio of net income (NPM) on the stock price. stock prices and the effect of earnings per share (EPS) on stock prices studied in the property sector Bura Efek Indonesia 2017 to 2019